Hubungan Panjang Berat Dan Faktor Kondisi Relatif Lima Spesies Ikan di Sungai Suwi Muara Ancalong, Kutai Timur - Nugroho, Rudy Agung; Florentino, Apri Pauci; Lariman, Lariman; Aryani, Retno; Rudianto, Rudianto; Kusneti, Monica (Universitas Atma Jaya Yogyakarta, 2021)
The length-weight relationship of fish and the condition factor provides an overview of the fish growth conditions in the river. The purpose of this study was to determine the length-weight relationship and factor condition of five fish species in the Suwi River wetlands. The method of catching fish used gill nets, ceiling nets, fishing rods, traps, and other nets. The research was conducted for to months in the Suwi river wetlands. The results the length-weight relationship of five fish were varied, Ompok bimaculatus had b value 2,93, Helostoma temminckii (b value 2.15), Mystus nemurus (b value 2,62), and Channa) micropeltes (b 2.61) which indicated a negative allometric growth pattern. Meanwhile Leptobarbus hoevenii (b 3.12) was a positive allometric growth pattern. Negative allometric indicates growth in length faster than weight growth, thus the physical shape looks flattened, while positive allometric indicates growth in fish length slower than growth in fish weight. Based on the relative weight (Wr) of Ompok bimaculatus 101.28 ± 19.13, Helostoma temminckii 101.05 ± 15.51, Mystus nemurus 100.95 ± 14.84, Channa micropeltes 101.09 ± 14.14, Leptobarbus hoevenii 103.71 ± 34.57. Condition factor above 100, indicates sufficient food availability or low predator density